State of the Art of Anthocyanins: Antioxidant Activity, Sources, Bioavailability, and Therapeutic Effect in Human Health - Noelia Tena; Julia Martín; Agustín G. Asuero (MDPI AG, 2020)
The antioxidant activity of anthocyanins in food is well known. Numerous antioxidant assays have been proposed to measure the capacity of anthocyanins to prevent the oxidation process that naturally occurs. Different solvents, temperatures, and pH levels are applied in each assay, and these factors should be taken into account in order to obtain useful and reproducible results. The concentration and the structure of these compounds are directly related to their antioxidant capacity and their environment. However, the effectiveness of the anthocyanin ingestion against diseases is also influenced by its bioavailability. Novel methodologies that simulate the digestion process have been developed in order to facilitate the current knowledge of anthocyanins bioavailability. Studies highlight the potential synergy effect between parent compounds and their derivatives (metabolites, conjugated products, and microbe-generated metabolites). The aim of this review is to provide an overview of advantages and disadvantages of the most common methods to determine the antioxidant activity of anthocyanins, chemical structure, and concentration of these compounds in different edible fruits, vegetables, and plants; their bioavailability after intake; as well as the main therapeutic effect described in the scientific literature.